Analisis Kondisi Fisik dan Teknik Dasar Pemain Sepak Bola Klub Mahardhika Kecamatan Belik Kabupaten Pemalang - Hendry Bagus Prasetyo; Dani Slamet Pratama; Bertika Kusuma Prastiwi (YLPK Mahardhika, 2021)
The research method used is a survey, data collection techniques using tests and measurements with the Battery Test system. The data analysis technique used descriptive statistics. This type of research is descriptive quantitative. The population in this study were 20 U-18 mahardika soccer players. The instruments used in the physical condition test are: Leg and dynamometer, MFT, Standing Board Jump, 50 meter Sprint, Sit and Reach, Agility T-test, squat thrust, strock stand, shooting, catch the ruler. As for the basic technical tests, the tests used are: passing, dribbling and shooting. The results of descriptive statistics of the physical condition of Mahardika club soccer players get 5% (1 person) with the very good category. 35% (7 people) in the good category, 30% (6 people) in the moderate category, 20% (4 people) with the poor category and 10% (2 people) with the very poor category. In the basic engineering research results obtained 5% (1 person) in the very good category, 45% (9 people) in the good category, 15% (3 people) in the moderate category, 30% (6 people) in the poor category and 5% ( 1 person) in the very poor category. Based on the results of the study, it can be concluded that the physical conditions and basic techniques of Mahardika club soccer players fall into the moderate category. Suggestions given by researchers: 1) The trainer can make a better and more effective exercise program to improve physical condition and basic techniques. 2) Athletes are expected to be more serious in maintaining and improving basic physical and technical conditions.